2005
DOI: 10.1207/s15327574ijt0504_2
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Testing Technicians: Critical Issues for Professional Psychology

Abstract: The controversial practice of using unlicensed individuals to administered psychological tests has been questioned by some psychologists, professional organizations, state and provincial boards of psychology, state governments, departments of education, and third-party health care providers. This article provides an overview of the ethical, legal, and technical issues surrounding the controversy. On the basis of a review of these issues, recommendations are offered that are directed toward state and provincial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 40 publications
(41 reference statements)
0
8
0
Order By: Relevance
“…Furthermore, when a test is standardized by graduate-level administrators, psychological technicians without the same education could lower the validity and reliability of the test results. Finally, it is unknown if psychological technicians are aware of the importance of building and maintaining rapport with clients throughout testing, as well as how to interpret certain key behaviors in children, such as attention to tasks, frustration tolerance, and reflectivity (Hall, Howerton, & Bolin, 2005). However, the supervising psychologist is ultimately responsible for ensuring that these and other clinical skills are properly taught to and utilized by psychometrists.…”
Section: History Of Psychometrymentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, when a test is standardized by graduate-level administrators, psychological technicians without the same education could lower the validity and reliability of the test results. Finally, it is unknown if psychological technicians are aware of the importance of building and maintaining rapport with clients throughout testing, as well as how to interpret certain key behaviors in children, such as attention to tasks, frustration tolerance, and reflectivity (Hall, Howerton, & Bolin, 2005). However, the supervising psychologist is ultimately responsible for ensuring that these and other clinical skills are properly taught to and utilized by psychometrists.…”
Section: History Of Psychometrymentioning
confidence: 99%
“…According to DeLuca (1989), psychological technicians are used worldwide to administer and score psychological tests. However, Hall et al (2005) found that the use of technicians outside of the United States was unclear. They also conducted literature searches on PsycINFO and ERIC databases and yielded little published information on the use of technicians in other countries.…”
Section: History Of Psychometrymentioning
confidence: 99%
See 1 more Smart Citation
“…Increased collaboration between psychologists, test developers, and test publishers is warranted to increase the accessibility of the most updated tests in low-income areas. Also, test corporations, as well as test developers, must consider and publish the minimum examiner qualifications necessary for test administration, which should reflect those of the examiners in the standardization process (Hall et al, 2005). These stated qualifications must then be enforced to prevent unqualified users from purchasing and using restricted instruments.…”
Section: Collaboration With Test Publishing Corporationsmentioning
confidence: 99%
“…Although they must be trained and supervised by a qualified psychologist, this will likely be more cost-effective than having the psychologist perform all the assessment functions. See Hall, Howerton, and Bolin (2005) for a description of the ethical and legal issues related to using testing technicians, as this practice is still considered controversial.Work with other clinics or practices in the area to make sure that someone with assessment skills is available. This may require a practitioner to rotate locations on a daily or weekly basis.Whenever possible, refer clients to other practitioners who are qualified to handle the assessment.Consider the costs and benefits of having practitioners obtain more training in assessment.…”
Section: Assessment-related Problems Encountered By Practicing Psycho...mentioning
confidence: 99%